On‐the‐Job Reference Materials. Issue 6 (30th May 2019) - Unknown
Abstract : This is an abridged excerpt from the introduction of Manual of Water Supply Practices M50, Water Resources Planning, third edition (catalog No. 30050‐3E). The book is available from the AWWA Store (https://store.awwa.org ).